Turkish-Russian relations between economic rapprochement and political divergence - Ehab Sataar Ghoneim; Kadhim lafta khuhair (Global Scientific Publishing, 2024)
The Turkish-Russian relations are very strong relations with differences in nature, as the relationship between the two countries historically had a legacy of conflict, wars and competition. The relationship also witnessed a lot of development for economic interests, as relations were characterized in the period between (1991-2002) by a mixture of tension, crises, and cooperation in many ways. areas between them. The economic motive is considered the main factor for the Turkish-Russian rapprochement and preventing the deterioration and tension of relations, but economic rapprochement does not mean canceling the historical rivalry between them. Mutual visits between the leaders of Turkey and Russia have been repeated more than 10 times in recent years for trade exchange and economic cooperation and have become.
Keywords: become; cooperation; tension; competition